Photoshop Elements 5 for Windows - Carlson, Jeff (Visual quickstart guide., 2007)
Shows how to use Photoshop Elements to retouch, repair, publish, and add effects to digital photographs and graphics by altering such factors as lighting, composition, and texture, and through editing, cropping, and filtering.